A Supported Nickel Catalyst Stabilized by a Surface Digging Effect for Efficient Methane Oxidation. Issue 51 (18th November 2019) - Zhou, Huang; Liu, Tianyang; Zhao, Xuyan; Zhao, Yafei; Lv, Hongwei; Fang, Shi; Wang, Xiaoqian; Zhou, Fangyao; Xu, Qian; Xu, Jie; Xiong, Can; Xue, Zhenggang; et al.
Abstract: A surface digging effect of supported Ni NPs on an amorphous N‐doped carbon is described, during which the surface‐loaded Ni NPs would etch and sink into the underneath carbon support to prevent sintering. This process is driven by the strong coordination interaction between the surface Ni atoms and N‐rich defects. In the aim of activation of C−H bonds for methane oxidation, those sinking Ni NPs could be further transformed into thermodynamically stable and active metal‐defect sites within the as‐generated surface holes by simply elevating the temperature. In situ transmission electron microscopy images reveal the sunk Ni NPs dig themselves adaptive surface holes, which would largely prevent the migration of Ni NPs without weakening their accessibility. The reported two‐step strategy opens up a new route to manufacture sintering‐resistant supported metal catalysts without degrading their catalytic efficiency. Abstract : A surface digging effect of supported Ni NPs on an amorphous N‐doped carbon is described, during which the surface‐loaded Ni NPs etch and sink into the carbon support underneath to prevent sintering. The sinking Ni NPs could be transformed into thermodynamically stable and active metal‐defect sites for activation of C−H bonds for methane oxidation by simply elevating temperature.